Exploring the care needs of Iranian patients with cancer: a qualitative content analysis - Fariba Mazhari; Zohreh Khoshnood (BMC, 2021)
Abstract Background‏ Cancer is currently one of the most critical health problems worldwide. Different studies have shown that disease can reduce people's ability to take care of themselves and this makes them face many needs. Therefore, this study aimed to investigate unmet needs faced by patients with cancer‏. Methods This study employed a conventional, qualitative content analysis method. Data saturation was achieved after interviewing 13 participants in 15 interview sessions. With the in-depth semi-structured approach, the participants were asked to narrate their experiences of self-care needs in the process of disease. The collected data were analyzed using Graneheim and Lundman's method through the following steps: Construction of the units of analysis, construction of codes of meaning, condensation, extracting codes, and categorization (subcategories, categories, and the core category) ‏. Results‏ Data analysis revealed two main categories. The first category was "Deficiency in disease management" with three subcategories: "the need to get rid of annoying physical symptoms"," the need for a caregiver to help with the daily routine", and "feeling frustrated and giving up treatment". The second main category covered "the need for sympathetic and knowledgeable caregivers" with the following five subcategories:" the need for sympathy and interaction with the nurse", "the need to hear the truth about the illness ", "the need for appropriate therapeutic interaction from physicians", "Inadequate qualification of medical secretaries about the patient", and" need for advice from psychologists for psychological adaptation‏". Conclusion‏ The most critical need reported by the patients was the need for compassionate and informed caregivers. So nursing management and care with kindness, competence, and conscience is the fundamental right of patients with cancer. Identifying patients' needs and problems can be used as a background for increasing the knowledge and experience of nurses and providing care for patients with cancer‏.